The Histone H3K27 Demethylase UTX Regulates Synaptic Plasticity and Cognitive Behaviors in Mice - Tang, Gang-Bin; Zeng, Yu-Qiang; Liu, Pei-Pei; Mi, Ting-Wei; Zhang, Shuang-Feng; Dai, Shang-Kun; Tang, Qing-Yuan; Yang, Lin; Xu, Ya-Jie; Yan, Hai-Liang; Du, Hong-Zhen; Teng, Zhao-Qian; et al. (Frontiers in Molecular Neuroscience, 2017)
Histone demethylase UTX mediates removal of repressive trimethylation of histone H3 lysine 27 (H3K27me3) to establish a mechanistic switch to activate large sets of genes. Mutation of Utx has recently been shown to be associated with Kabuki syndrome, a rare congenital anomaly syndrome with dementia. However, its biological function in the brain is largely unknown. Here, we observe that deletion of Utx results in increased anxiety-like behaviors and impaired spatial learning and memory in mice. Loss of Utx in the hippocampus leads to reduced long-term potentiation and amplitude of miniature excitatory postsynaptic current, aberrant dendrite development and defective synapse formation. Transcriptional profiling reveals that Utx regulates a subset of genes that are involved in the regulation of dendritic morphology, synaptic transmission, and cognition. Specifically, Utx deletion disrupts expression of neurotransmitter 5-hydroxytryptamine receptor 5B (Htr5b). Restoration of Htr5b expression in newborn hippocampal neurons rescues the defects of neuronal morphology by Utx ablation. Therefore, we provide evidence that Utx plays a critical role in modulating synaptic transmission and cognitive behaviors. Utx cKO mouse models like ours provide a valuable means to study the underlying mechanisms of the etiology of Kabuki syndrome.